Does hypopituitarism recover when macroprolactinomas are treated with cabergoline? - Karavitaki, N; Dobrescu, R; Byrne, J; Grossman, AB; Wass, J (2013)
Objective The frequency and the degree of recovery of anterior pituitary hormone deficits in patients with macroprolactinoma responsive to cabergoline are not clear. Our aim was to evaluate pituitary function in these patients with particular reference to an assessment of the possible restoration of pituitary deficits. Subjects and Methods The records of all subjects prospectively presenting to our Department with macroprolactinomas treated with cabergoline over a 2-year period were reviewed. Pituitary function was assessed at diagnosis and, if abnormal, for three consecutive years for the GH, FSH/LH and ACTH axes, and at 3 years for the TSH axis. Results Twelve patients were included. Severe GH deficiency was found in 83% at diagnosis and did not resolve in any patient at last assessment. Gonadotrophin deficiency was found in 90% at diagnosis and in 50% at last evaluation (showing reversal in 44% of deficient patients, all achieved within 1 year). ACTH deficiency was found in 17% at diagnosis and it did not reverse in any patient at last assessment. TSH deficiency was found in 36% at diagnosis and in 27% at last assessment (reversal in 25% of deficient patients). Conclusions In our study, in a group of patients with macroprolactinoma systematically assessed at intervals, pituitary dysfunction in response to cabergoline was found to be mostly irreversible, except for the gonadotroph axis which showed restoration in a subset of subjects following achievement of normoprolactinaemia. It would appear that the reversibility of pituitary axes may be less common than previously thought. © 2012 John Wiley and Sons Ltd.